Peran Economic Order Quantity dalam Manajemen Persediaan Bahan Baku (Studi pada UD. Nurisma tahun 2016) - Dianita Meirini; Praptiwi Praptiwi (Accounthink, 2017)
This research aims to determine the role of the inventory management method, Economic Order Quantity (EOQ) in decision making for the amount of economic ordering and cost efficiency of raw material inventory. EOQ method is very effective applied to companies that have a high quantity of annual inventory. UD. NURISMA is a manufacturing company producing “krupuk uyel mentah” with annual demand of raw material is high enough, which is 3,423 sacks in 2016. This research was conducted at UD NURISMA for inventory cost efficiency and the determination of order quantity economical raw material inventory of “krupuk uyel mentah”. This research is a quantitative descriptive research and using raw material inventory data at UD. NURISMA which includes data on the quantity of raw material requirements, data of ordering cost and raw material storage data during 2016. This study compares raw material inventory management based on UD. NURISMA policy with EOQ inventory management.The result of this research is EOQ inventory management method is able to give efficiency of inventory cost equal to Rp 3,082,502, -. The cost efficiency is obtained from the difference between inventory cost based on UD NURISMA policy (Rp. 9.338.178,-), toward inventory cost with EOQ (Rp. 6.255.676,-). Researchers suggest UD. NURISMA to use the Economic Order Quantity (EOQ) method. Implementation of EOQ method provides benefits for the company to know how much raw materials to be ordered and when to make a re-order.